IMPLEMENTASI KEGIATAN PRAMUKA DALAM PEMBENTUKAN MORAL PESERTA DIDIK DI SMP NEGERI 1 NUSAWUNGU - Sunu Latifudin; Efi Miftah Faridli; Ratna Kartikawati (Jurnal Pendidikan Sultan Agung, 2025)
This study aims to analyze the implementation of scouting activities in the formation of students' morals at SMP Negeri 1 Nusawungu. The study was conducted at SMP Negeri 1 Nusawungu with 2 teacher participants and 4 grade VIII students. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. To obtain objective data validity, the analysis technique uses the triangulation source credibility test. This study uses the Miles and Huberman technique, namely data collection, data reduction, data presentation and data conclusion. The results of the study indicate that scouting activities play an important role in the formation of students' moral character through training in discipline, responsibility, cooperation, and religious and nationalistic values. However, there are several obstacles such as low participant participation, minimal supporting facilities, and lack of motivation. Strategies taken to overcome these obstacles include mentor training, a personal approach to students, and alignment of scouting activities with the curriculum. The implications of this study indicate that scouting can be an important instrument in character education if managed effectively and sustainably.